Safety and immunogenicity of plant-produced African horse sickness virus-like particles in horses - (:unkn) unknown (My University, 2018)
AbstractAfrican horse sickness (AHS) is caused by multiple serotypes of the dsRNA AHSV and is a major scourge of domestic equids in Africa. While there are well established commercial live attenuated vaccines produced in South Africa, risks associated with these have encouraged attempts to develop new and safer recombinant vaccines. Previously, we reported on the immunogenicity of a plant-produced AHS serotype 5 virus-like particle (VLP) vaccine, which stimulated high titres of AHS serotype 5-specific neutralizing antibodies in guinea pigs. Here, we report a similar response to the vaccine in horses. This is the first report demonstrating the safety and immunogenicity of plant-produced AHS VLPs in horses.
Keywords: African Research